PENGGUNAAN BIJI JAGUNG KUNING REBUS SEBAGAI SUPLEMEN ENERGI DALAM RANSUM SAP! PERAH LAKTASI TERHADAP KINERJA PRODUKSI DAN KOMPOSISI SUSU = THE EFFECT OF COOKED CORN SUPPLEMENTATION AS SOURCE OF ENERGY IN THE DIET OF ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
In lactating dairy cows, energy demand is important to sustain milk production. This trial was carried out to study the effect of cooked corn supplementation as source of energy in the diet of lactating dairy cows on milk production and composition. The trial was conducted in farm group of Sido Makmur, Jambu, Cangkringan, Sleman, using 12 multiparous lactating cows ( Â±16 weeks post partum) for 8 weeks. They were divided into two groups of 6 cows. Group 1 (K1) was supplemented by ground cooked corn of 200 g/I of milk produced, while Group 2 (K2) as a control group without supplementation. Both group of cattle were given concentrate at the level 1 kg/2 litre of milk produced, while forage was given ad libitum. Drinking water was provided freely. Daily milk production and feed intake were recorded. Milk composition (total solid, solid non fat, fat content) was measured at the early, middle and the end of the trial, while body weight was measured two times at the early and at the end of the trial. All data collected was analyzed by t-test. The results obtained indicated that feed intake from forage and concentrate was not differ significantly between groups, but total dry matter intake (13.1 vs. 10.8 kg), TDN (7.6 vs. 5.8 kg) and crude protein intake (1.36 vs. 1.18 kg) were higher in treatment group than control due to corn supplementation. Daily milk production (10.75 vs. 9.30 I) and average daily gain (0.42 vs. 0.28 kg) tend to be higher in K1. Milk composition (total solid and fat content) was not affected by treatment, but solid non-fat was significantly (P